Aplikasi Sistem Informasi Jadwal Penerbangan Pesawat Berbasis SMS - Sigit Sugiyanto (JUITA : Jurnal Informatika, 2010)
Along with technological development, more and more people take advantage of mobile phone use, particularly for users who are busy and do not have much time. Therefore Information System Application Based Aircraft Flight Schedule SMS made to facilitate people in finding a good flight schedule information anytime and anywhere, which may be in day-to-day had other. This application uses J2SE technologies because these technologies are multi-platform and allows for developers to be able to create a multi-platform wireless applications, which can be implemented on a mobile phone, which supports Java applications. This application system to provide flight data directly or indirectly flight quickly and precisely, in helping people to obtain information on flight schedules to suit individual needs. Especially for people who have high mobility who do not have enough time to spare to come to the airport so it can save time, effort and cost.